Influence of Phaseolus vulgaris blossoming characteristics and canopy structure upon reaction to Sclerotinia sclerotiorum - Schwartz, Howard F.; Steadman, James R.; Coyne, Dermot P. (Scientific Societies, 1978)
Bean (Phaseolus vulgaris) lines or cultivars with indeterminate growth habit produced more blossoms, and had more colonized senescent blossoms than did those with determinate growth habits, but senescent blossoms accumulated within and around both types; thus, many potential sites for colonization by Sclerotinia sclerotiorum were present in both. However, disease severity was not always correlated with frequency of colonizable sites. The structure of a dry edible bean canopy affected white mold disease incidence and severity. The most susceptible entries produced a canopy that was significantly more dense in terms of leaf area × dry weight/height than was that of resistant types. The growth habit of the plant; i.e., determinate or indeterminate, did not exclusively influence the incidence of infection. The more critical determinant of disease severity was conferred by the distribution of the leaf area, especially near the ground. Bean germplasm can be screened in the greenhouse for reaction to S. sclerotiorum if suitable methodology is utilized.